Kurdish Students’ Attitudes Towards the Use Of Films In Teaching Literary Works In EFL Classroom - Berivan M. A. Abdullah; Ivan H. Murad; Herjin F. Abdullah (JEELS (Journal of English Education and Linguistics Studies), 2020)
The current study investigates Kurdish students’ attitudes towards the use of films in teaching literary works at universities in the Kurdistan Region of Iraq. The study also highlights whether using films in teaching literary works is beneficial or not and what challenges are faced by them. The data were collected by using questionnaires and interviews from 60 students aged between 18-24 years old from both private and public universities. Out of 60 students, 15 were randomly chosen to be interviewed. Results show that some students consider teaching literary works using films is beneficial, as it encourages students to study and read more literary works and it also makes them actively interact with the content which helps them remember the events more effectively. However, the study also reveals that some Kurdish students consider teaching literary works using films is a waste of time, and this discourages interaction between students and their teacher. In addition, ‘boredom’ and ‘language difficulty’ are the other two major challenges faced by Kurdish students.